بناء دالة الاستهلاك للاقتصاد الجزائري للفترة 2000-2023 - مقراني احمد لمين (جامعة الوادي University of Eloued, 2025)
"تيدؼ ىذه الدارسة إلى تحميؿ دالة الاستيلاؾ في الاقتصاد الجازئري خلاؿ الفترة (0202-0222)، باستخداـ نموذج الانحدار الخطي البسيط ونموذج الانحدار الخطي المتعدد في اطار طريقة المربعات الصغرى العادية، تعتمد عمى النظريات الاقتصادية الكينزية،نظريةالدخؿالدائـ(فريدماف)،ونظريةدورةالحياة.وشممتمتغيارترئيسيةمثؿ الاستيلاؾ )C( ، الناتج المحمي الإجمالي)GDP( والدخؿ السابؽ)1-yt( ، وقد خمصت الدارسة تؤكد أىمية الدخؿ كمحدد رئيسي للاستيلاؾ في الجازئر This study aims to analyze the consumption function in the Algerian economy during the period (2000-2023), using a simple linear regression model and a multiple linear regression model within the framework of the ordinary least squares (OLS) method. It is based on Keynesian economic theories, the permanent income hypothesis (Friedman), and the life-cycle theory. Key variables included consumption (C), gross domestic product (GDP), and lagged income (yt−1). The study concluded by emphasizing the importance of income as a key determinant of consumption in Algeria.
ماستر
Keywords: دالة الاستيلا; الاقتصاد الجازئري; الاستيلاؾ العائمي; البرنامج القياسي (EVIEW; Consumption function – Algerian economy – Household consumption – EVIEWS